PENGARUH VARIASI PRODUK DAN POTONGAN HARGA TERHADAP PENJUALAN SMARTPHONE MEREK VIVO - Pasaribu, Herlina Feronika; Panjaitan, Fani Renta Uli; Sirait, Ronnie Togar Mulia (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
The purpose of this study is to ascertain how price reductions and product changes affect the quantity of Vivo brand smartphones sold in 234 ACC Tarutung outlets. A questionnaire was utilized as the data gathering tool, and descriptive quantitative with probability research methods were applied. 85 respondents who purchased Vivo smartphones from 234 ACC The study's sample consisted of Tarutung outlets. The analysis process includes validity, reliability, hypothesis testing, and coefficient of determination using SPSS 26. According to the partial results, the discount variable had a positive and significant impact on sales volume with a tcount > ttable value (3.380 > 1.989), and the product variety variable had a positive and significant effect on the sales volume of Vivo brand smartphones at 234 ACC Tarutung stores with a tcount > ttable value (2.560 > 1.989). with either a sig or a value of fcount > ftabel (40.018> 3.11). value of 0.000, the study's findings concurrently demonstrate that the discount and product variety variables had a positive and significant impact on the sales volume of Vivo brand smartphones at 234 ACC Tarutung stores.